1984
DOI: 10.1007/bf01871066
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane potential of Lettré cells does not depend on cation gradients but on pumps

Abstract: The plasma membrane potential of Lettré cells has been determined with the optical indicator oxonol-V and found to be -57 mV at 37 degrees C (range -20 to -80 mV depending on the physiological condition of the cells). Increasing extracellular K+ does not depolarize cells: even in the presence of 155 mM K+ the potential is -41 mV; membrane potential is also insensitive to the chemical gradient of Na+, Mg2+, Ca2+ or Cl-. Ouabain depolarizes the cells; H+ efflux from cells is stimulated by extracellular Na+. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

1984
1984
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…In our experiments the impairment of sodium and potassium gradients did not induce histamine release but facilitated the secretagogue-effect of antigen, compound 48/80 or ionophore A23 187. In contrast the inhibition of sodium-potassium ATPase in neuronal cells (Vizi et al, 1982) and in chromaffin cells (Pocock, 1983) (Bashford & Pasternak, 1984) indicated that electrogenic pump(s) can generate membrane potential. In these cells increasing extracellular KCI up to 80 mM did not modify membrane potential whereas ouabain depolarized the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…In our experiments the impairment of sodium and potassium gradients did not induce histamine release but facilitated the secretagogue-effect of antigen, compound 48/80 or ionophore A23 187. In contrast the inhibition of sodium-potassium ATPase in neuronal cells (Vizi et al, 1982) and in chromaffin cells (Pocock, 1983) (Bashford & Pasternak, 1984) indicated that electrogenic pump(s) can generate membrane potential. In these cells increasing extracellular KCI up to 80 mM did not modify membrane potential whereas ouabain depolarized the membrane.…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies, which are greater at high lactate concentrations, have been noted previously for the transport of lactate into hepatocytes (Edlund & Halestrap, 1988), and may reflect the presence of an anionic pathway capable of driving lactate out of the cell under the influence of the membrane potential, particularly when it is present at high concentrations. Such a pathway is thought to exist in striated muscle (Mason, 1986) and Lettre cells (Bashford & Pasternak, 1984).…”
Section: Isolation Of Cardiac Ventricular Myocytesmentioning
confidence: 99%
“…However, the median microvillous Em measured in villi isolated from term placentas bathed in C02-HC03-(pH 7 4) buffer at 37°C is -22 mV (Greenwood et al 1993a) (Bashford & Pasternak, 1984) (Leichtweiss, Carstensen, Schroder & Rachor, 1985). Na+ concentration was 84 mmol 1-F and K+ concentration 62 mmol 1-' in non-perfused, and 85 and 61 mmol 1-' in perfused placentas, respectively.…”
Section: Cell Characterization Immunocytochemistrymentioning
confidence: 99%